1983
DOI: 10.1111/1523-1747.ep12519602
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting a Role for Immune Complex-Mediated Inflammation in the Pathogenesis of Bullous Lesions of Systemic Lupus Erythematosus

Abstract: Evidence supporting an immune complex pathogenesis of bullous lesions in systemic lupus erythematosus includes immune deposits, acute inflammation, and blister formation at the cutaneous basement membrane zone. Since cutaneous immune deposits are a general feature of lupus, an attempt has been made to determine whether deposits in lupus patients with blisters are functionally different from those in patients without blisters. Skin was obtained from 4 consecutive patients with blisters and 14 controls. The grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Studies have shown they are able to activate the C-system and mediate C-dependent migration and adherence of leukocytes to the BMZ. Furthermore, cutaneous immune deposits in the perilesional skin of patients with bullous SLE activate C and generate C-derived inflammatory mediators to a significantly greater degree than the deposits in uninvolved skin from the same patients or the deposits in SLE patients without blisters [6].…”
Section: Pathogenesis Of Bullous Slementioning
confidence: 98%
See 4 more Smart Citations
“…Studies have shown they are able to activate the C-system and mediate C-dependent migration and adherence of leukocytes to the BMZ. Furthermore, cutaneous immune deposits in the perilesional skin of patients with bullous SLE activate C and generate C-derived inflammatory mediators to a significantly greater degree than the deposits in uninvolved skin from the same patients or the deposits in SLE patients without blisters [6].…”
Section: Pathogenesis Of Bullous Slementioning
confidence: 98%
“…The bullous SEE phenotype is composed of a characteristic set of clinical, histologic, immunohistologic (DIF), and IEM features that develop in a patient who meets the American Rheumatism Association's (ARA) classification criteria for SLE [4,5,13]-Most patients have been young black women, but all ages, races, and both sexes are affected [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The clinical features include a widespread, non-scarring vesiculobullous eruption that may occur on, but is not confined to, sun-exposed skin.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations